LITERATUR REVIEW : STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN SUMBER DAYA MANUSIA PADA ABAD 21 - Apremedian, Apremedian; Ana Rifatun; Alma Wiyarti; Rani Setyawati; Yatini, Yatini; Ngurah Ayu Nyoman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The 21st century demands high-quality human resources in the education sector to face global challenges. This literature review aims to analyze school principal leadership strategies in developing human resources based on several recent studies. The method used is a literature review of several national and international journals. The results show that transformational and instructional leadership styles significantly influence teacher performance, job satisfaction, and the quality of education. Strategies such as providing motivation, creating a collaborative culture, and developing digital literacy are keys to successful HR development in schools. In conclusion, effective principal leadership is a primary catalyst in improving the quality of human resources in the 21st-century education era. Keywords: Principal Leadership, Human Resource Development, 21st Century Education.